Exploring the physical and psychological effects of maternal death on midwives in a selected hospital of Vhembe District Limpopo Province - Mofe, Nancy (My University, 2024)
BACKGROUND Maternal mortality is a global problem mostly influenced by pregnancy related conditions or its management. Regardless of the availability of resources in some institutions, maternal death results in midwives exhibiting signs of physical, emotional, and psychological trauma. METHOD The study adopted qualitative explorative descriptive research designed to explore the physical and psychological effects of maternal deaths among midwives working in a selected public hospital at Vhembe district, Limpopo Province. A non-probability snowball sampling was used to select participants who participated in this study. Data in this study was collected through semi structured interviews. The interviews were recorded, transcribed, and analysed using a thematic content analysis method. The data collected was further submitted to the independent coder to confirm the study findings. Measures of Trustworthiness were maintained in the study. RESULTS From the study, three themes and 16 sub-themes emerged. The findings of this study indicate that midwives experienced physical and psychological health issues manifested as loss of appetite, insomnia, social isolation, avoidant behaviour, depression, and anger. CONCLUSION The physical and psychological effects of maternal death impact the quality of maternal healthcare rendered by midwives. In view of this, midwives need to be supported in different ways such as counselling, debriefing, training and being provided with all the necessary resources they need to enable them to cope with the adverse event of a maternal death.
Thesis (M. Nur. (Nursing Science)) -- University of Limpopo, 2024
Keywords: Coping; Maternal death; Midwives; Psychological effects; Physical effect; Midwives; Maternal health services; Mothers -- Mortality; Psychological debriefing; Health -- Psychological aspects